81.3k views
5 votes
Rewrite the polynomial-9x^5+36x^4+189x^3 in factored form, using the factoring method method you prefer.

User Sherb
by
5.6k points

2 Answers

3 votes

Answer:

The answer is -9x^3(x - 7) (x+3)

Rewrite the polynomial-9x^5+36x^4+189x^3 in factored form, using the factoring method-example-1
User Guille
by
5.3k points
3 votes

The polynomial 9x^5+36x^4+189x^3 in factored form is
-9 x * x * x *(x-7) *(x+3)

Solution:

Given, polynomial equation is
-9 x^(5)+36 x^(4)+189 x^(3)

We have to find the factored form of the above given polynomial equation.

Let us solve it by grouping.

Now, take the polynomial ⇒
-9 x^(5)+36 x^(4)+189 x^(3)

By taking common term out, we get


\rightarrow-9 x^(3)\left(x^(2)-4 x-21\right)


\rightarrow-9 x^(3)\left(x^(2)-(7-3) x-7 * 3\right)

Grouping the terms we get,


\rightarrow-9 x^(3)\left(\left(x^(2)-7 x\right)+(3 x-7 x^3)\right)

Taking common terms out from each group,


\rightarrow-9 x^(3)(x(x-7)+3(x-7))


\Rightarrow-9 x^(3)((x-7)(x+3))


\rightarrow-9 x * x * x *(x-7) *(x+3)

Thus the factored form of polynomial is found out

User Marc Pursals
by
5.7k points